RELIGIOSITY AND FOREIGN DIRECT INVESTMENT: THE CASE OF ROMANIA - Sebastian D. TOCAR (Cross-Cultural Management Journal, 2019)

(untitled)
This paper presents a quantitative approach to the analysis of the impact of cultural factors on Foreign Direct Investment (FDI). FDI is indispensable for the economic development of Eastern European countries, including Romania. In turn, FDI is determined by a multitude of factors, including cultural ones. Religiosity is an extremely important cultural factor since religion defines culture. However, the religious factor seems to be avoided in the context of FDI research. This study proposes an original reliable indicator designed to quantify religiosity –the Religiosity Index based on the review of literature in the field. This construct is analyzed as a cultural factor with an influence on FDI through simultaneous equations modeling. This allowed the author to identify the significant relationships in the multitude of bilateral and complex interrelations of FDI determinants.